Keputusan Pembelian Kosmetik Halal Ditinjau Dari Brand Image, Harga, Performance SPG Dan Kualitas Produk - Lestari, Yunia Ike; Diharto, Awan Kostrad; Wulandari, Fitri (Fakultas Ekonomi - Universitas Setia Budi, 2023)
Fluctuations in consumer decisions in buying halal cosmetics (especially Wardah) are interesting because there are many factors that influence this decision. This study uses four independent variables (Brand Image, Price, SPG Performance, and Product Quality) which are thought to influence consumer decisions in buying Wardah cosmetics. The research method used in this study is a quantitative method with a questionnaire. The population in this study were consumers who had purchased wardah cosmetic products with a non-probability sampling technique using purposive sampling. The sample criteria used in this study are consumers who live in Surakarta and have purchased Wardah cosmetic products. The results showed that Brand Image, SPG Performance, and Product Quality proved to have a significant positive effect on Wardah's cosmetic purchasing decisions. However, the price variable has no effect on the decision to purchase Wardah cosmetics.